EDUKASI PEMANFAATAN KELOR DAN IKAN LELE SEBAGAI ALTERNATIF PERBAIKAN STATUS GIZI BALITA STUNTING - Sa’adah Handayani; Resty Himma Muliani; Nina Maria Desi; Ratna Dewi Handayani; Fitriana Rakhimah (Jurnal Pengabdian kepada Masyarakat Cahaya Negeriku, 2024)
Background: The urgent nutrition problem in Indonesia is closely related to stunting in children. Indonesia itself is a tropical country that has a diversity of plants that are rich in nutrients of economic value, one of which is Moringa (Moringa oleifera). Despite being rich in nutrients, people dislike the consumption of moringa because it has a strong odor caused by protease enzymes. Various elements of macro and micro nutrients in moringa leaves are not widely known by the Indonesian people, this is important in an effort to increase knowledge about the benefits and modification techniques of moringa leaves to be combined with animal protein from catfish into processed nuggets that can prevent and improve the nutritional status of stunting toddlers.. Method: The methods used in this activity giving pretest about the benefits of moringa and Clarias Gariepinus, providing knowledge to cadres about stunting and how to prevent it, discussion and question and answer about the material that has been presented, Administering post-test assessments as a way to evaluate activities . Results Wilcoxon test results there is an effect of cadre knowledge about the benefits of moringa, clarias gariepinus with stunting with a p value of 0.000. Conclusion: This community service improvement activity has significant results in increasing knowledge for posyandu cadres from less knowledge as much as 75% (pretest) to good knowledge 25% (posttest).